Change in Act Number 16 Of 2019 As An Amendment to Law Number 1 of 1974 Islamic Law and Gender Perspective - Rangkuti, Muhammad Yusuf; Agustar, Armi (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
Law Number 1 of 1974 concerning Marriage, which stipulates a difference in the minimum age of marriage of 19 years for men and 16 years for women. It is considered unfair based on gender equality, even though in the 1945 Constitution of the Republic of Indonesia in Article 27 paragraph (1) it is said that, every citizen simultaneously has his position in law and government. Thus, Law Number 1 of 1974 concerning Marriage, causes discrimination against women, and hinders the fulfillment of women's constitutional rights. Such things as the right to health, education and equality in the eyes of the law. So that the birth of Law Number 16 of 2019 concerning Marriage, in this case, the minimum limit for carrying out marriage. Providing justice to the age of marriage, between a 19-year-old male and female.